Safety Evaluation of Branched-Chain Amino Acids in Centropomus Viridis Brain Cells: In Vitro Assay. - Avalos-Soriano , A.; Soto-López , M.J; Castañeda , M.S.; Betancourt-Martínez , N.D.; Moran- Martínez J.3, J.3 (Revista de Ciencias Médicas Torreón, 2026)
Branched-chain amino acids (BCAAs), composed of L- leucine, L-isoleucine, and L-valine, are essential amino acids in the nutrition of various animal species, including marine fish. Traditionally considered precursors of protein synthesis, BCAAs also act as key signaling molecules and metabolic modulators. Although its physiological role has been widely studied, information on its toxicity and safety, especially in fish cell systems, remains limited. The species Centropomus viridis, due to its high dietary requirements of amino acids, represents a relevant model to explore the effects of BCAAs on brain cells in an in vitro environment. Immortal cultures of Centropomus viridis brain cells were established from juvenile specimens, following standardized protocols of enzymatic disintegration and seeding in 96-well plates. The cells were kept in L-15 medium supplemented with 10% fetal bovine serum and antibiotics, incubated at 25 °C without CO2. The treatments consisted of exposure to BCAAs solutions (L-leucine, L-isoleucine, and L-valine) at concentrations of 50, 100, 250, 500, 1000, 2500, 5000 and 1 0000 μg/mL, instantly prepared from sterile stocks. Negative controls (cells without BCAAs) and positive controls were included. Cell viability was assessed using the MTT assay, adding 10μL of MTT solution (5 mg/mL) per well and measuring absorbance at 570 nm after 4 hours of incubation. Additionally, trypan blue exclusion was performed by incubating the cells with the dye for 5 minutes and counting viable and non-viable cells under light microscopy. The evaluation criteria included percentage of viability with respect to the negative control and observation of cell morphology. BCAA treatments even at concentrations of 1000, 2500, 5000 and 10000 μg/mL did not produce significant alterations in cell viability, with percentages greater than 95% compared to the negative control. No morphological changes or increase in trypan blue exclusion ABSTRACT were observed. At the maximum concentration evaluated (5000 and 10000 μg/mL), no decrease in viability was detected (up to 95% of live cells), without reaching criteria of significant cytotoxicity or evident morphological damage. The positive control showed a reduction in viability of less than 60%, validating the sensitivity of the experimental system. Therefore, the cellular safety limit for BCAAs in this line is above 5000 and 10000 μg/mL, with no appreciable adverse effects above this threshold. The results obtained coincide with the few previous reports in mammals, where BCAAs present low toxicity even at high concentrations. The absence of relevant cytotoxic effects in brain cells of Centropomus viridis suggests a wide tolerance to these amino acids, in accordance with the physiological needs of marine species with high protein requirements. However, the literature indicates a lack of controlled studies in humans and other species, which makes it difficult to extrapolate these data to broader clinical and dietary contexts. This study demonstrated that branched-chain amino acids are harmless and safe for brain cells of Centropomus viridis under in vitro conditions, even at elevated concentrations of up to 10000 μg/mL. The methodology used, based on MTT assays and exclusion of trypan blue, provides robust criteria for the toxicological evaluation of nutritional supplements in marine fishes. These findings contribute to knowledge about food safety in aquaculture and highlight the need to expand research to other cell systems and species, as well as to generate comprehensive metabolic and toxicological data to establish accurate recommendations on the use of BCAAs in animal and human feed.